The Utilization of the Statue Building Museum as a Source of Learning Batak Literature - Nurfadillah Tul Zannah Siregar; Sakti Ritonga (Edumaspul: Jurnal Pendidikan, 2024)
This study examines the Utilization of the Statue Building Museum as a Learning Resource for Batak Literature. The purpose of this study is as a medium to find out the usefulness of museums as a source of learning. This study uses a qualitative approach with a descriptive method. The informants in this study are museum heads, academics, students/students. Data collection is carried out through observation, interviews, and documentation. The results of the study show that the history of the establishment of the North Sumatra State Museum located on Jl. H.M. Joni No.51 Daoed Joesoef, Minister of Education and Culture, on April 19, 1982. However, President Ir. Soekarno laid the first stone, a pair of ceremonies, in 1954. Since then, the museum has also been called the Sculpture Building. The building of this museum is shaped like a traditional house of North Sumatra. The front roof is decorated with ornaments from the Batak Toba, Simalungun, Karo, Mandailing, Pakpak, and Nias tribes. The use of the collection at the North Sumatra State Museum as a source of learning about Batak Literature for researchers can be seen from the use of these historical sources as the main source and has the main goal, namely to improve previous research. The collections in the museum contribute greatly to research, so that many meanings are revealed about the study of Batak literature.